2018
DOI: 10.1371/journal.pone.0195098
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of Streptococcus pneumoniae, Haemophilus influenzae, Moraxella catarrhalis, and Staphylococcus aureus in Indonesian children: A cross-sectional study

Abstract: Streptococcus pneumoniae is an important cause of infection and commonly colonizes the nasopharynx of young children, along with other potentially pathogenic bacteria. The objectives of this study were to estimate the carriage prevalence of S. pneumoniae, Haemophilus influenzae, Moraxella catarrhalis, and Staphylococcus aureus in young children in Indonesia, and to examine interactions between these bacterial species. 302 healthy children aged 12–24 months were enrolled in community health centers in the Bandu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 34 publications
6
73
2
2
Order By: Relevance
“…Dual carriage of H. influenzae and M. catarrhalis strongly associated with S. pneumoniae carriage which in turns associated with M catarrhalis carriage. These results are consistent with those of several studies conducted among children with upper RTIs [38][39][40]. In these studies, the competitive interaction between S. pneumoniae and H. influenzae was dependent on neutrophils and complement.…”
Section: Discussionsupporting
confidence: 93%
“…Dual carriage of H. influenzae and M. catarrhalis strongly associated with S. pneumoniae carriage which in turns associated with M catarrhalis carriage. These results are consistent with those of several studies conducted among children with upper RTIs [38][39][40]. In these studies, the competitive interaction between S. pneumoniae and H. influenzae was dependent on neutrophils and complement.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with those of many recent studies, where, after introduction of the Hib conjugate vaccine, Hib has rarely been found in the upper respiratory tract of children, or as a cause of invasive disease, while the incidence of carriage and disease with NTHi strains has proportionally increased. 3,17,18 Furthermore, the carriage prevalence of NTHi in nasopharyngeal cultures varies according to the age, disease, geographic location, crowding, and socioeconomic factors of individuals. 18,19 A recent study from 12 European countries investigated the epidemiology of invasive H. influenzae disease trend according to its serotype and patient age during 2007 to 2014.…”
Section: Discussionmentioning
confidence: 99%
“…3,17,18 Furthermore, the carriage prevalence of NTHi in nasopharyngeal cultures varies according to the age, disease, geographic location, crowding, and socioeconomic factors of individuals. 18,19 A recent study from 12 European countries investigated the epidemiology of invasive H. influenzae disease trend according to its serotype and patient age during 2007 to 2014. 15 The study indicated that the mean annual notification rate was 0.6 cases/100,000 individuals, with an increasing annual trend of 3.3%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This multidrug-resistant (MDR) bacteria may cause pneumonia, sepsis, meningitis, otitis media (O'Brien et al 2009;Mirza et al 2011;Hu et al 2016;Cherazard et al 2017), bloodstream infections and sinus infections in young children (CDC 2017). In Indonesia research on people with pneumococcal infection has already been carried out in the following areas: Jakarta (Yuliarti et al 2012), Bandung, Central Lombok, and Padang West Sumatera (Dunne et al 2018). The prevalence of carriers of S. pneumoniae among the healthy population has been sharply increasing ( DKP-Jateng 2014; Farida et al 2014;Ditjen P2P 2018) and multidrugresistant bacteria can pose a growing threat to general health (Lestari et al 2012).…”
Section: Introductionmentioning
confidence: 99%